De loin on dirait une île - Holder, Éric 1960- (Dilettante, 2008)
Description of the author's time spent in the Medoc and the characters he met there.
Keywords: Holder, Eric -- Travel; Holder, Éric -- 1960-; Autobiographical Narrative; Médoc (France); Médoc; Autobiografie